The relationship cost benefit of the provision of housing: towards a reconceptualization of the real estate model in Mexico - González Gabriel, Luis (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
This work emphasizes the indivisible relationship between those concepts related to the social phenomenon of housing from the perspective of the optimal use of energy, their economic impact on construction systems, highlighting the importance associated with the comfort of the built space without forgetting the welfare of the inhabitants. For practical purposes, this text raises the possibility of conceiving a built environment of social interest that allows a radical change in the mentality of those who plan, promote and inhabit housing is considered. The foregoing is supported by a comparative and qualitative analysis of the characteristics of construction companies, distinguishing between them the applicability of the time-dependent heat transfer model, the incorporation of passive air conditioning methods and the type of construction in itself.